The Influence of Service Quality, Store Atmosphere, and Experiential Marketing on Customer Loyalty at Famicafé Tenggilis Surabaya - Novitasari, Mayhana Dwi; Purwanto, Sugeng (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Competition in the retail business has become a highly competitive and dynamic arena in the global economy. The intense competition among retail businesses encourages them to compete for consumer interest and market leadership by devising various strategic plans to increase competitive advantage. FamilyMart, under PT Fajar Mitra Indah, is one of the retail businesses currently competing to win the market in Indonesia. FamiCafé, created by FamilyMart is a brand extension that combines the concept of a minimarket with a cafe. This research examines the effect of service quality, store atmosphere, and experiential marketing on customer loyalty at FamiCafé Tenggilis Surabaya. This research uses quantitative methods involving 108 respondents selected from the population of FamiCafé Tenggilis Surabaya customers. Nonprobability sampling with a purposive sampling approach was used for sample selection. Data was collected through distributing questionnaires and measured using a Likert scale. The data analysis process uses Partial Least Squares (PLS) analysis tools with the help of SmartPLS software. Based on the research findings, it was revealed that service quality affects customer loyalty at FamiCafé Tenggilis Surabaya, store atmosphere has no effect on customer loyalty at FamiCafé Tenggilis Surabaya, and experiential marketing affects customer loyalty at FamiCafé Tenggilis Surabaya.